(untitled) (J-AGENT (Journal of Agricultural Engineering and Technology), 2024)
The Raised bed is a farming method that can be applied to narrow land using containers or tubs Sprinkler irrigation is one of the methods to provide water by spraying water into the air, falling to the ground like rainwater. This study aims to design a sprinkler irrigation system for Shallots on raised beds and determine the response of Shallots to the sprinkler irrigation method applied. The research method is experimental with field experiments on Raised bed land with 4 raised bed plots. Parameters observed were discharged, sprinkler irrigation beam distance, crop water requirements, plant growth, and soil physical properties. The results showed that the sprinkler irrigation design was not successfully applied to narrow land because it had a relatively broad water distribution. The results showed that the water requirement of the shallot plant on day 18 was 1.8 mm/day and the lowest on day 10 was 0.9 mm/day. The soil analysis results at the research location for the texture of sandy loam soil for manure media and plant residue media. The field capacity of manure media was 29.74%, plant residue media was 63.19, the permanent wilting point of manure media was 17.99 %, plant residue media of 19.30%, and soil permeability values ​​were moderate to moderately fast class on manure media and a relatively fast class on plant residue media. The results showed that Shallots gave a good response, which can be seen in the average number of leaves at the highest 6.27 strands. The average increase in plant height reached the highest value of 31.56 cm.